García Fernández, Emilio C. (2025). Viaje cinematográfico por Galicia: Una retrospectiva emocional (1896-1939), Editorial Fragua, Madrid, ISBN: 9791399121872. 991 pp. - Diez Puertas, Emeterio (Historia y Comunicación Social, 2026)
Reseña